Harmonisation, Decentralisation and Local Governance: Enhancing Aid Effectiveness - Klaver, Dieuwke; Wageningen International; Tibamwenda, Assumpta I.; Consultant (Wageningen UR Centre for Development Innovation., 2009)
During the last decades, international development assistance was often marked by overlaps, duplication of efforts and rivalry between multitudes of donor organisations. In order to translate the principles of the Paris Declaration into practice in the field of Local Governance and Decentralisation (LGD), different donor organisations have joined forces on headquarter level and formed a working group, the Development Partners Working Group for Local Governance and Decentralisation (DPWG-LGD), which is operating since 2006. InWEnt is hosting the secretariat of the group since 2008 and assigned Wageningen International to organise two lead donor workshops. The workshop drew a cross section of delegates who comprised development partners, consultants, academicians, members of parliament and local governance practitioners. The partner countries included Rwanda, Ghana, Tanzania and Uganda whose experiences were mutually re-enforcing and beneficial.
Keywords: Harmonisation; Decentralisation; Local governance